2017
DOI: 10.1002/2017gl073901
|View full text |Cite
|
Sign up to set email alerts
|

Observation of pulsating aurora signatures in cosmic noise absorption data

Abstract: This study investigates the contribution of energetic (E > 30 keV) particle precipitation during a pulsating aurora event over Kilpisjärvi (L = 6.2) on 26 February 2014. It is based on the comparison of auroral blue‐line emission (427.8 nm) data from an all‐sky camera and cosmic noise absorption (CNA) data obtained from a multibeam experiment of the Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA) riometer. The data sets are compared for three KAIRA beams close to magnetic zenith. Results show a clear co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 44 publications
1
37
1
Order By: Relevance
“…Although pulsations in CNA during the recovery phase have been reported before (Grandin et al, 2017), no evidence of CNA pulsations are seen in any of the growth-phase events reported in this study. One possible reason is that the pulsation region is relatively narrow in latitude in the growth phase.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Although pulsations in CNA during the recovery phase have been reported before (Grandin et al, 2017), no evidence of CNA pulsations are seen in any of the growth-phase events reported in this study. One possible reason is that the pulsation region is relatively narrow in latitude in the growth phase.…”
Section: Discussioncontrasting
confidence: 49%
“…Satellite-based observations suggest that they are caused by time-varying flux of high-energy (> 10 keV) electrons (Wing et al, 2013). Weak pulsations in the CNA with close correlation to the optical phenomena have been reported (Brekke, 1971;Grandin et al, 2017).…”
mentioning
confidence: 99%
“…Precipitation can occur also during pulsating aurora and exhibit modulation at similar timescales as the auroral emission (e.g. Grandin et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Later, several statistical analyses confirmed that pulsating aurora is often associated with CNA (e.g., Arnoldy et al, ; Brekke, ). Recently, Grandin et al () showed an event in which there was a one‐on‐one correlation between the auroral pulsations quantified by the auroral blue‐line emission (427.8 nm) from an all‐sky camera and the variations in CNA obtained from a multibeam experiment of the Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA; McKay‐Bukowski et al, ).…”
Section: Introductionmentioning
confidence: 99%